Soil drench treatment with ß-aminobutyric acid increases drought tolerance of potato. - Anita Sós-Hegedűs; Zsófia Juhász; Péter Poór; Mihály Kondrák; Ferenc Antal; Irma Tari; Brigitte Mauch-Mani; Zsófia Bánfalvi (PLoS ONE)
The non-protein amino acid β-aminobutyric acid (BABA) is known to be a priming agent for a more efficient activation of cellular defence responses and a potent inducer of resistance against biotic and abiotic stresses in plants. Nevertheless, most of the studies on priming have been carried out in Arabidopsis. In potato, the effect of BABA was demonstrated only on biotic stress tolerance. We investigated the effect of BABA on the drought tolerance of potato and found that soil drenched with BABA at a final concentration of 0.3 mM improves the drought tolerance of potato. Water loss from the leaves of the primed plants is attenuated and the yield is increased compared to the unprimed drought-stressed plants. The metabolite composition of the tubers of the BABA-treated plants is less affected by drought than the tuber composition of the non-treated plants. Nitric oxide and ROS (reactive oxygen species) production is increased in the BABA-treated roots but not in the leaves. In the leaves of the BABA-treated plants, the expression of the drought-inducible gene StDS2 is delayed, but the expression of ETR1, encoding an ethylene receptor, is maintained for a longer period under the drought conditions than in the leaves of the non-treated, drought-stressed control plants. This result suggests that the ethylene-inducible gene expression remains suppressed in primed plants leading to a longer leaf life and increased tuber yield compared to the non-treated, drought-stressed plants. The priming effect of BABA in potato, however, is transient and reverts to an unprimed state within a few weeks.